The advertisement call of Rhinella granulosa (Anura, Bufonidae) - São-Pedro, Vinícius Avelar; Medeiros, Pedro Henriques; Garda, Adrian Antonio (Zootaxa, 2011)
The Rhinella granulosa species group was taxonomically reviewed by Gallardo (1965) and most recently by Narvaes and Rodrigues (2009). This last review recognized twelve species (Rhinella granulosa, R. pygmaea, R. bergi, R. major, R. mirandaribeiroi, R. azarai, R. nattereri, R. fernandezae, R. dorbignyi, R. merianae, R. humboldti, R. centralis) distributed along the open habitats of South America and Panama (Narvaes & Rodrigues, 2009). Recently, a new species (R. bernardoi) was described from San Juan province, in Argentina (Sanabria et al., 2010). Both revisions and the description paper were based on morphological and morphometric characteristics. Despite the relevance of acoustic parameters in anuran taxonomy, the advertisement call of only one species of the R. granulosa group has been formally described. Köhler et al. (1997) described the vocalization of Rhinella major from Bolivia, considered at that moment as the subspecies Bufo granulosus mini. Herein we describe the advertisement call of Rhinella granulosa, a species occurring in the Caatinga domain of northeastern Brazil according to Narvaes and Rodriguez (2009).